Oxidation of Binary Mixtures of 1,3-Dialkylthiourea and Thiourea: Formation of 3-Amino-4-Alkyl-5-Alkylimino-Δ2-1,2,4-Thiadiazolines - V. Nair, Sheena (Asian Journal of Chemistry, 2010)
Oxidation of a binary mixture of unsymmetrical dialkyl thiourea and thiourea yield the intennediate bis(formamidine)sulphide which rearranges into two amidinothioureas. From the final oxidation product it can be inferred that the migration terminal of the unsubstituted amidino group is regulated by the steric factor and the electronic effect of the substituents on the amidino group.